Major causes of domestic accidents in children: a descriptive-exploratory study - Regiane Paiva de Lima; Lorena Barbosa Ximenes; Emanuella Silva Joventino; Luiza Jane Eyre de Souza Vieira; Mônica Oliveira Batista Oriá (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Domestic accidents can be considered a public health problem due to their high morbidity and mortality rates. The aims of this descriptive-exploratory study with a quantitative approach were to identify domestic accidents involving children in their first infancy, and to know their major causes. The sampling enrolled 65 families of children registered in two day-care centers in Fortaleza-CE, during 2004-2005. Parent's interviews were conducted at the domiciles, using forms to assess demographic and domestic accident referrals. No significant association was found between the child sex and the type of accident. However, significant associations were found between the type of accident and age and between the kind of accident suffered and the part of the body injured. Thus, knowing the major accidents that reach the children at the domiciliary context and their causing effects are critical for nurses to develop efficiently health educative strategies towards accident prevention and child health promotion.